Digitization Of 3d Tote Bag With Contemporary Batik Motif Of Keris Siginjai - Siagian, Grace Ekklesia; Rachman, Anung (Corak, 2022)
Technological advances now require students to be more creative and improve their digital skills. However, it cannot be separated from this hand expertise in sketching is still needed even though there is the technology. Also, the need to use the concept will later be related to digitising 3d tote bags with contemporary batik motifs keris siginjai. In the design of this final project, work through visualization of the siginjai kris as the main object by doing a visual depiction in the form of a siginjai kris as a contemporary batik motif inserted into a denim-based tote bag. The methods applied are redefining, Design Thinking, and Prototyping methods. Making 3-Dimensional digitization of a product design can make it easier for respondents to display the final form of a product design.